TOPONIMI BENTANG ALAM DALAM PANTUN MELAYU TERBITAN BALAI PUSTAKA - Febriani, Rizkyqa Nor (Jurnal Tradisi Lisan Nusantara, 2024)
This research is motivated by the existence of toponymy in Malay poetry editor of the library. The toponymy that is examined in this study is in the form of the meaning of toponymy in Malay poet-ry.   The use of toponymy in the collection of Malay poems published by the editorial of the li-brary has certain effects that need to be studied further as well as its suitability as an alternative to literature teaching materials in high school. This study aims to: 1) describe toponymy in Malay poetry editor of the library; 2) describe Malay poetry as an alternative teaching material for lit-erature in grade VII of junior high school. This type of research is Qualitative. The data collec-tion technique is the Listen Method. Data Card and Data Tabulation Instruments, and Data Valid-ity Testing are carried out using the Triangulation Technique to increase validity in qualitative research, as well as data analysis techniques, namely the samples studied in this study are sorted and selected using purposive sampling. Based on the results of the analysis that has been carried out in this study, it can be concluded that (1) there are two categories of toponymy, namely artifi-cial toponymy which includes; countries, capitals, districts, provinces, cities, sub-districts, and sub-districts. The toponymy of landscapes that include: islands, continents, mountains, and lakes. The toponymy has a relationship of meaning found in the sampiran and the content. (2) The col-lection of Malay poems of the library can be used as an alternative to literature teaching materi-als in high school because it contains linguistic aspects that are easy to understand, aspects of maturity of the soul that can affect students' interests and willingness, and aspects of cultural background that can provide moral and educational value to students.